In search of the Way: Christian brotherhood of struggle and its programme - Ekaterina Gudilina (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article studies the ideology of the religious and political organisation Christian Brotherhood of Struggle, which existed in the period from 1905 to 1908 and represents a vivid example of the Russian religious revival. The Christian Brotherhood of Struggle not only formulated the views on socio-economic and political relations through the prism of Christianity, but also made attempts at active political struggle for putting the church ideal into practice. The programme of the Christian Brotherhood of Struggle (the Programme of the Brotherhood, a number of “addresses” of the Brotherhood to the public, as well as the essays Vzyskuyushchim Grada ‘To those Looking for the City’, Pis’ma ko Vsem ‘Letters to All’, and Khristianskoe otnoshenie k vlasti i nasiliiu ‘Christian Attitude to Power and Violence’) contain a religious and social ideal, the reconstruction of which is the purpose of the article. The interaction between social and religious elements in the construction of the ideal led to the Brotherhood’s peculiar vision of the concepts of Christian society and Christian public service, of freedom and violence, of true communication and the election principle. According to the Christian Brotherhood of Struggle, individual salvation should be supplemented by an active struggle for the religious and social ideal and by the involvement of the church and believers in the political sphere and in the struggle for power. The vision of the Christian Brotherhood of Struggle of an ideal structure of society is a specifi c mixture of utopian, “necessarily fi nal ideal”, fi lled with eschatological expectations, with real policy that takes into account the needs and requirements of the individual and guarantees fundamental rights and freedoms. The stance of the Christian Brotherhood of Struggle about distinguishing in its Programme the programme-minimum in the economic and political spheres only emphasised the features of the Christian policy, which extends not only to the spiritual sphere of social relations, but also to the whole society. At the same time, an exclusively instrumental approach to religion and the church, the aspiration to use them in politics can lead to the desacralisation and devaluation of these phenomena of social life.